Adaptasi Harimau Sumatera melalui Rekayasa Prostetik Wajah dalam Pembuatan Karya Rias Fantasi - Anisyah, Aini; Widowati, Trisnani; Windayani, Novia Restu (Panthera : Jurnal Ilmiah Pendidikan Sains dan Terapan, 2026)
The visual adaptation of the Sumatran Tiger into fantasy facial makeup art is a strategic alternative media for the conservation campaign of this endangered species. This study aims to describe and analyze the feasibility of a prosthetic fantasy facial makeup work that adapts the anatomical and aesthetic elements of the Sumatran Tiger. The type of research used is descriptive quantitative. The data collection technique was through a performance assessment test of the work. The research instrument was an assessment rubric validated by three experts using the Aiken's V index and its reliability was analyzed with Cronbach's Alpha (0.889). The results showed that the average content validity of the instrument was 0.859 (85.9%). The quality of the prosthetic fantasy makeup work obtained an average value of 88.89% which is included in the "very appropriate" category. The meaning and visual representation indicators obtained the highest value (94.44%), indicating that the prosthetic technique is very effective in conveying symbolic messages and conservation values. The conclusion of this study is that prosthetic engineering is able to visualize the characteristics of the Sumatran Tiger realistically and dramatically, and meets the standards of aesthetic quality, creativity, and technique in the field of makeup. The use of three-dimensionality allows for more realistic facial manipulation than conventional makeup.